Cerebrospinal fluid leakage costs after craniotomy and health economic assessment of incidence reduction from a hospital perspective in the Netherlands - Chris van Lieshout; Geert W J Frederix; Emma M H Slot; Ahmet Kinaci; Mare H Kollen; Eelco W Hoving; Tristan P C van Doormaal (BMJ Open)
Objectives We aim to quantify the cost difference between patients with incisional cerebrospinal fluid (iCSF) leakage and those without after intradural cranial surgery. Second, the potential cost savings per patient when a decrease in iCSF leakage rate would be achieved with and without added costs for preventative measures of various price and efficacy are modelled.Design Health economic assessment from a hospital perspective based on a retrospective cohort study.Setting Dutch tertiary referral centre.Participants We included 616 consecutive patients who underwent intradural cranial surgery between 1 September 2017 and 1 September 2018. Patients undergoing burr hole surgery or transsphenoidal surgery, or who died within 1 month after surgery or were lost to follow-up were excluded.Primary and secondary outcome measures Outcomes of the cost analysis include a detailed breakdown of mean costs per patient for patients with postoperative iCSF leakage and patients without, and the mean cost difference. For the scenario analyses the outcomes are the potential cost savings per 1000 patients when a decrease in iCSF leakage would be achieved.Results Mean cost difference between patients with and without iCSF leakage was €9665 (95%CI, €5125 to €14 205). The main cost driver was hospital stay with a difference of 8.5 days. A 25% incidence reduction would result in a mean cost saving of −€94 039 (95% CI, −€218 258 to −€7077) per 1000 patients. A maximum cost reduction of −€653 025 (95% CI, −€1 204 243 to −€169 120) per 1000 patients could be achieved if iCSF leakage would be reduced with 75% in all patients, with 72 cases of iCSF leakage avoided.Conclusions Postoperative iCSF leakage after intradural cranial surgery increases healthcare costs significantly and substantially. From a health economic perspective preventative measures to avoid iCSF leakage should be pursued.